How much can we afford to lose?. Issue 2 (5th May 2016) - Savage, Kathryn S.
Abstract : Synopsis: This case focusses on internal controls necessary to prevent theft of cash collections. Troy Wheeler, assistant dean of the School of Business and Public Policy was asked to write a memorandum to the university's internal auditor verifying that controls on the cash register in the school were adequate to prevent major theft. Troy wrote the memo, but the request awakened nagging concerns regarding the cash register. The more Troy thought about it, the more concerned he became about the potential for loss. Troy needed to identify the major weaknesses in the existing system and make feasible recommendations to improve control. Research methodology: This case is based on the author's personal association with the organization, observation, interviews of key figures in the case, and examination of relevant documents. Relevant courses and levels: This case is appropriate for any graduate or undergraduate accounting class where internal controls are analyzed and documented. The case could be used in courses on internal or external auditing or accounting information systems.